Violent victimisation, professional self-esteem, and punitivity of German police officers - Ellrich, Karoline (Policing and society, 2018)
To date, punitive attitudes of police officers have received only little attention in criminological research. The present study addresses this lack of research by investigating punitivity in German police officers. Focus is placed on violent victimisation, which has been commonly considered to be a main cause of punitive attitudes. Furthermore, this study examined whether police officers’ professional self-esteem is related to punitivity and serves as a protective factor that buffers the negative effect of violent victimisation on punitivity. Ordinary least square regression analyses based on a sample of 15,733 German police officers support a relationship between victimisation experiences and punitivity. Police officers who had been violently attacked within the last year reported higher levels of punitivity than non-victims. Moreover, respondents with repeated victimisation experiences were the most punitive. While higher levels of professional self-esteem were indeed associated with less punitivity, the suggested protective influence of police officers’ professional self-esteem could not be confirmed. By contrast, higher levels of self-esteem instead increased the negative effects of victimisation experiences on punitivity.